KEDUDUKAN SAKSI DALAM HUKUM PIDANA - Remincel Remincel (Ensiklopedia of Journal, 2019)
The process of examination of the witnesses began from the investigation to the prosecution at the trial level. In the first stages of the investigation, the witnesses were questioned by investigators with due regard to the protection of witnesses, ie, without threats or tekanan.dari any party. Then the witness may be examined at the residence of the witness and the witness examined without being sworn. While at the level of prosecution or pesidangan the first witnesses called to hear the information.